Students’ Use of Memory Strategies in Learning English Pronouns - Sri Novaliza; Siti Awaliyah Ramadhanti; Mariyasih Mariyasih; Masagus Firdaus (English Education and Literature Journal (E-Jou), 2026)
This study examines the effectiveness of various memory-enhancement strategies in helping 9th-grade students at Al-Quran Darul Ulum Junior High School improve their mastery of English pronouns. Through an analysis of usage frequency and students’ strategy preferences, this study reveals a strong relationship between cognitive memory aids and improved grammar skills. The findings highlight three prominent techniques, repetition, mnemonics, and contextual association, as highly effective methods that enable students to transition from rote memorization to a deeper, more practical understanding of pronouns within sentence structures. Ultimately, this study demonstrates that students who apply these methods are far more proficient in correctly identifying and using pronouns in everyday situations. This implies that effective language instruction must shift from conventional memorization exercises to targeted memory aids that align with the brain’s natural way of absorbing and retaining new language elements